Voluntaryism within the Established Church in Nineteenth Century Belfast - Kerr, S. Peter (Studies in church history, 1986)
‘The Irish need to be governed and controlled as well as I excited.’ So wrote Daniel Wilson, a young English clergyman later to be bishop of Calcutta, after visiting Armagh in June 1814 to discuss with local clergy the possibility of setting up a branch of the Church Missionary Society. An Irish (Hibernian) Church Missionary Society, he argued, would … have a tendency both to revive and regulate the piety of members of the Church, fostering whatever is holy and energetic, and yet directing both in … orderly submission to the Church …